Aerosol Jet Deposition for Structured Materials. (December 2020) - Tsui, Lok-Kun; Garzon, Fernando; Plumley, John
Abstract : The roots of Aerosol Jet Printing (AJP) materials trace back to the development of digital inkjet printing. Pressure driven, continuous flow methods for inkjet printing were first developed at Stanford University by R. Sweet in the 1960s and led to a number of continuous flow printing technologies by the 1970s. Electrostatic control was used to guide the trajectory of continuously flowing ink drops. The drops were either directed to the print media or deflected into a gutter. These systems required the recirculation of the unused ink, adding considerable system complexity.